The first term of a particular sequence , while the subsequent term for is defined as:
Find the real value of that satisfies .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Note that U 0 = 0 , U 1 = 1 , U 2 = 3 , U 3 = 7 ... It appears that
U n − U n − 1 k = 1 ∑ n U k − k = 1 ∑ n U k − 1 k = 0 ∑ n U k − k = 0 ∑ n − 1 U k ⟹ U n = 2 n − 1 = k = 1 ∑ n 2 k − 1 = k = 0 ∑ n − 1 2 k = 2 n − 1
Let us prove by induction that the claim U n = 2 n − 1 is true for all n ≤ 0 .
Proof:
Therefore, we have U 2 0 1 7 x 2 0 1 7 − 1 = 2 2 0 1 7 − 1 x 2 0 1 7 − 1 = 1 . ⟹ x = 2 .